Developing Character-Based Reading materials for The Eighth Year Students of SMP Negeri 1 Singaraja in The Academic Year of 2012-2013 - ., I GEDE WIMI SUPUTRA; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Prof. Dr. I Nyoman Sudiana, M.Pd (Universitas Pendidikan Ganesha, 2013)
This study is a Research and Development study (R&D) which aimed at developing Character-Based Reading Material for the eighth year students of SMP Negeri 1 Singaraja in the academic year of 2012-2013. This study used Sugiyono?s model of Research and development. Based on the syllabus analysis and the existing reading materials, the result shows that the existing reading material has some weaknesses in terms of its feature, content, language used, and exercises. These weaknesses were supported by the result of questionnaire administered to the students which is showed that 62.50% of the students strongly disagree and 37.50% disagree that the existing reading material covered character values. Based on the result of the analysis, the researcher developed Character-Based Reading materials which covers three genres and each genre consists of four reading passage. The values introduced in the texts were 16 values or characters which are proposed by the Board of National Education Standard (BSNP), comply with School Based Curriculum, the criteria of good material proposed by Tomlinson (2012). Based on the result of analysis on the quality of Character-Based Reading material it was found that the result of rubric administered to the students showed that the quality of Character-Based Reading materials were considered as Good materials while based on teacher?s result, the quality of Character-Based Reading material were considered as Excellent material. The final product of this study was the Character-Based Reading materials for the eighth year students of SMP Negeri 1 Singaraja which involves reading passage and varieties of exercises related to the reading passage.keyword : character, reading material, character-based reading material